A Study of Employers’ Satisfaction With Generation Z in Thai Workplaces - Ngotngamwong, Rachaniphorn; Suvannasing, Supanya (Human Behavior, Development and Society, 2024)
The newest generation of workers, Generation Z, differs in many ways from previous cohorts, and so its entry into job markets poses increasing management challenges for organizations. The objective of this qualitative phenomenology research study was to explore employers’ challenges and satisfaction levels with Gen Z in the workplace. Conducted in Thailand, a total of 13 participants participated in in-depth structured interviews. The results showed that while there were challenges working with Gen Z, the majority of employers were satisfied with their performance in the workplace. Gen Z workers were described as being creative, fast, problem-solvers, self-learners, tech savvy, highly confident, flexible, adaptable to change, and bringing new and great ideas. Their challenges included low organizational commitment, reluctance to stay beyond normal working hours, impatience, lack of attention to detail, and lack of some social and basic office skills. This study provides a better understanding of Gen Z’s mindset, and the input gained may help employers to respond more appropriately to changes in their current workforces. It may also be valuable in helping universities to better prepare students for the workplace.